Analysis of mode II interlaminar fracture of multidirectional laminates - Morais, A.B. de
A numerical study was performed on the mode II interlaminar critical strain energy release rate (GIIc) of multidirectional laminates. The objectives were to define appropriate specimen stacking sequences and to predict variations of GIIc with the delaminating interface. Three-dimensional finite element (FE) analyses of the end-notched flexure (ENF) test showed that the mode III component resulting from anticlastic effects can be minimised with thick unsymmetrical specimens. It is also predicted that GIIc may be substantially higher for multidirectional specimens than for the most common [0º]n unidirectionals. This could prevent valid GIIc measurements, due to premature yielding and intraply failure. Various experimental studies confirm these predictions.